2021
DOI: 10.3390/polym13071006
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Wastes Functionalized Biomaterials from Micro to Nano: A Cleaner Approach for a Sustainable Environmental Application

Abstract: The exponential increase in textile cotton wastes generation and the ineffective processing mechanism to mitigate its environmental impact by developing functional materials with unique properties for geotechnical applications, wastewater, packaging, and biomedical engineering have become emerging global concerns among researchers. A comprehensive study of a processed cotton fibres isolation technique and their applications are highlighted in this review. Surface modification of cotton wastes fibre increases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 160 publications
0
13
0
Order By: Relevance
“…Cellulose can be classified into two types according to the production origin. There is cellulose from plant biomass, which stands out as a source of raw material for the production of bio-based fuels, paper, packaging and biomedical applications [ 77 , 78 ]. Cellulose is derived from a variety of microorganisms such as fungi, algae ( Valonia ventricosae, Glaucocystis ), and bacterial strains belonging to the genera Agrobacterium, Aerobacter, Achromobacter, Sarcina, Acetobacter, Rhizobium, Salmonella and Azotobacter that produce acetic acid [ 79 , 80 , 81 ].…”
Section: Bacteria Cellulose: An Innovative Biomaterialsmentioning
confidence: 99%
“…Cellulose can be classified into two types according to the production origin. There is cellulose from plant biomass, which stands out as a source of raw material for the production of bio-based fuels, paper, packaging and biomedical applications [ 77 , 78 ]. Cellulose is derived from a variety of microorganisms such as fungi, algae ( Valonia ventricosae, Glaucocystis ), and bacterial strains belonging to the genera Agrobacterium, Aerobacter, Achromobacter, Sarcina, Acetobacter, Rhizobium, Salmonella and Azotobacter that produce acetic acid [ 79 , 80 , 81 ].…”
Section: Bacteria Cellulose: An Innovative Biomaterialsmentioning
confidence: 99%
“…Nanocellulose-based aerogel is known for its high porosity, ultralow density and excellent absorption capacity [ 11 ]. As a biopolymer, cellulose is a biodegradable, cost-effective and ecofriendly substance, and developing nanocellulose aerogel only consumes a tiny amount of cellulose due to the high porosity of aerogels [ 12 ]. Thus, the past few years witnessed a significant increase in the studies that utilize nanocellulose as precursor material in aerogel fabrication for different absorption applications.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported that some of these challenges that limit the application of seaweed biopolymer for packaging can be overcome by the incorporation of cellulose nanocrystals (CNCs) into the polymer matrix to improve the mechanical and barrier properties [12]. Studies have been reported using micro crystalline cellulose (MCC) as a reinforcement agent for improved packaging [13].…”
Section: Introductionmentioning
confidence: 99%